COFFEE BREWERS' COLLECTING POINT BRAND REGISTRATION ASSISTANCE IN EFFORTS TO PROTECT INTELLECTUAL PROPERTY RIGHTS - Putri Saphira Audesti Binti Yussofi; Febri Jaya (ConCEPt - Conference on Community Engagement Project, 2022)
In the world of trade, brands as a form of intellectual property rights have been used hundreds of years ago and have an important role because brands are used to distinguish the origin of goods and services. Brands are also used in the world of advertising and marketing because the public often associates an image, quality and reputation of goods and services with certain brands. A brand can be a very valuable asset commercially and often it is the brand that makes a product expensive or even more valuable than the company. The purpose of this study is to analyze the legal protection assistance for trademark registration on the product of the Point of Gathering Coffee Brewers in the city of Batam. The method used puts forward normative legal research with a prescriptive model. The collected legal materials will be studied comprehensively and analyzed deductively with a systematic presentation.